Assessing Prospective Physics Teachers' Inquiry Skills in Post-Pandemic: Rasch Analysis - Wahyudi; Setiawan, Agus; Suhandi, Andi; Samsudin, Achmad; Bin Kamin, Yusri (Jurnal Pendidikan IPA Indonesia, 2024)
Inquiry skills are essential for prospective physics teachers. Inquiry skills are a necessary in the educational curriculum because they can help students construct scientific knowledge and skills, essential activities in science learning. This research aims to validate the scientific inquiry skills test used to evaluate the scientific inquiry skills of prospective physics teachers. This research used a quantitative method with a cross-sectional survey design. The adapted inquiry skills test questions consisted of 35 items covering nine aspects of inquiry skills. The participants in this research were 168 prospective physics teachers who were chosen randomly and came from educational institutions on the islands of Indonesia. The results show that the adapted inquiry skills test meets the validity and reliability criteria based on Rasch parameters. On average, students' skills are still low in answering inquiry skills test questions. Analysis of differential item function reveals that the inquiry skills test items contain minimal biases based on university category and gender but are slightly larger based on semester level. The inquiry skills scores of students in semesters II, IV, and VI were not significantly different. The inquiry skills scores of male students are significantly different from the inquiry skills scores of female students. The adapted inquiry skills test instrument has met the criteria of validity, reliability, and slight bias based on university category and gender. A small number of test items need to be corrected so they are not biased based on the student's semester level. The evaluation results show that male students show better inquiry skills than female students. Reorganization is needed in planning and implementing learning strategies that can facilitate the inquiry skills of prospective physics teachers.